Strategi Peningkatan Kinerja Operasional Bongkar Muat Peti Kemas: Studi Kasus di PT Jakarta International Container Terminal: Performance Improvement Strategy of Container Operation Terminal Case at Jakarta International Container Terminal - Nova Oktavia; Marimin Marimin; Yandra Arkeman (Jurnal Aplikasi Bisnis dan Manajemen (JABM), 2020)
PT JICT is largest container terminals at Tanjung Priok and has capacity of container up to four million TEUs(Tweenty Foot Equivalent). To compete with other container terminal at Tanjung Priok, JICT needs to evaluate and determine strategy for improving operational performance. The purposes of this research is to indetify internal factor and external factor that influence operational performance at PT JICT and to determine priority of alternative strategy to improve operation container terminal performance.This study used 4 analysis tools matrix i.e. IFE (Internal Factor Evaluation) and EFE (External Factor Evaluation), BSC (Balanced Scorecard), AHP (Analytical Hierarchy Process), and Analytical Network Process ( ANP). The result showed that position JICT in quadran I with weigh (3.79; 3.16) indicated that JICT phase in grow and build. The results of BSC and AHP showed that perspective of the customer is the first priority that influence operational performance improvement with a weight of 0.48. The main priority alternative strategies generated by using the ANP method to improve operational performance are maintenance of operational facilities and equipment on a regular schedule as well as investing in new operational equipment with a weight of 0.0321. Keywords: AHP, ANP, BSC, Operation of loading unloading container